Bioprocessing of bio-based chemicals produced from lignocellulosic feedstocks. (December 2016) - Kawaguchi, Hideo; Hasunuma, Tomohisa; Ogino, Chiaki; Kondo, Akihiko
Abstract : Graphical abstract: Highlights: Bio-based chemicals have been produced from lignocellulosic biomass by SHF, SSF, and CBP. Lignocellulosic feedstocks are more recalcitrant to bioprocessing than starch. Bio-based chemicals serve as biopolymeric building blocks for polyester and polyimide. More complete utilization of lignocellulose is needed for efficient bioprocessing. Abstract : The feedstocks used for the production of bio-based chemicals have recently expanded from edible sugars to inedible and more recalcitrant forms of lignocellulosic biomass. To produce bio-based chemicals from renewable polysaccharides, several bioprocessing approaches have been developed and include separate hydrolysis and fermentation (SHF), simultaneous saccharification and fermentation (SSF), and consolidated bioprocessing (CBP). In the last decade, SHF, SSF, and CBP have been used to generate macromolecules and aliphatic and aromatic compounds that are capable of serving as sustainable, drop-in substitutes for petroleum-based chemicals. The present review focuses on recent progress in the bioprocessing of microbially produced chemicals from renewable feedstocks, including starch and lignocellulosic biomass. In particular, the technological feasibility of bio-based chemical production is discussed in terms of the feedstocks and different bioprocessing approaches, including the consolidation of enzyme production, enzymatic hydrolysis of biomass, and fermentation.